Expression and alternative splicing of folate pathway genes in HapMap lymphoblastoid cell lines. (April 2009) - Duan, Shiwei; Huang, R Stephanie; Zhang, Wei; Mi, Shuangli; Bleibel, Wasim K; Kistner, Emily O; Cox, Nancy J; Dolan, M Eileen
Aim: Folate is vital for cell growth and development through its important role in one-carbon metabolism –– an essential process in the synthesis of amino acids and nucleic acids. Folate pathway genes have been considered as therapeutic targets of drugs for the treatment of cancer and other diseases. Racial and ethnic disparities of folate metabolism and outcome of antifolate therapies have been reported. In this study, we evaluate the genetic regulation for expression and alternative splicing of folate related genes in HapMap lymphoblastoid cell lines (LCLs) of individuals of European and African descent.Materials & methods: Gene and exon level expression and alternative splicing of folate pathway genes were compared in LCLs derived from the Centre d''Etude du Polymorphisme Humain (CEPH) from Utah (CEU) and the Yoruba from Ibadan (YRI) using a permutation-based test. A genome-wide association study was performed to search for SNPs associated with folate pathway gene expressions and alternative splicing in the combined population samples.Results: A total of 52 folate pathway genes were evaluated in the analysis of which 46 were expressed in the LCLs. There were 12 genes (26%) with differential gene-level expression and 23 genes (50%) with differential alternative splicing for exons or UTRs between the CEU and the YRI (permutation p ≤≤ 0.05). The expression level of FPGS and the splicing indices of eight genes ( ATP13A2, ASCC3L1, IFIH1, SMARCA5, SMARCA2, SETX, DDX52 and RUVBL2 ) were found to be associated with SNP genotypes in the combined populations (p < 3.2 ×× 10 -8, Bonferroni corrected p < 0.05).Conclusion: Our study suggests that LCLs are an in vitro system suitable to evaluate the expression levels of folate pathway genes. The differential transcript-level expressions and the differentially alternative splicing events of exons or UTRs and associated SNP markers in 2 populations will enhance our understanding of the folate pathway and, thus, facilitate research in the areas of nutrition and folate metabolism.